Return on equity: A popular, but flawed measure of corporate financial performance - J. H.V.H. De Wet; E. Du Toit (South African Journal of Business Management, 2007)
This article is aimed at analysing the impact of popular financial performance measures on shareholders' wealth. It tests the strength of the linear relationships between these performance measures and shareholders' returns, which consist of dividends and changes in the share price. The return on equity (ROE) is weighed up against the present favourite, economic value added (EVA) and the merits and flaws of each approach are discussed. Other approaches, such as a combination of performance measures and the expectations theory are also discussed briefly.The statistical tests performed found Spreads (a standardised EVA) to be slightly superior to ROE in explaining changes in shareholders' returns. However, the use of same year data resulted in very weak linear relationships between all the performance measures tested, relative to shareholders' returns.When 5-year medians were used in the analysis, significant correlations were obtained between current shareholders' returns and the future results for the internal performance measures. This engenders some support for the expectations theory with its contention that the most effective positive impact on shareholders' returns can be accomplished by managing expectations about future financial results, rather than maximising these results now. It is clear that the debate about the effectiveness of traditional accounting performance measures, as well as the search for the real drivers of shareholder value, will continue and increase in intensity.
Keywords: 650